Effects caused by the spinal administration of ketamine S (+) 5% with no preservatives, using a single puncture, and located on the spinal cord and meninges in rabbits - Lima Filho, José Admirço (2014)
PURPOSE: To evaluate the effect of ketamine S (+) 5% with no preservatives and administered as a subarachnoid single puncture on the spinal cord and meninges of rabbits.METHODS: Twenty young adult female rabbits, each weighing 3500-5000 g and having a spine length between 34 and 38 cm, were divided by lot into two groups (G): 0.9% saline in G1 and ketamine S (+) 5% in G2, by volume of 5 μg per cm column (0.18 mL). After intravenous anaesthesia with ketamine and xylazine, the subarachnoid space was punctured at S1-S2 under ultrasound guidance, and a random solution was injected. The animals remained in captivity for 21 days under medical observation and were sacrificed by decapitation. The lumbosacral spinal cord portion was removed for immunohistochemistry to assess the glial fibrillary acidic protein (GFAP), and histology was assessed using hematoxylin and eosin (HE) stain.RESULTS:No histological lesions were found in the nervous tissue (roots and cord) or meninges in either group.CONCLUSION: The ketamine S (+) 5% unpreserved triggered no neurological or histological lesions in the spinal cord or meninges of rabbits.